The role of temporal predictability in semantic expectation: An MEG investigation. (July 2015) - Lau, Ellen F.; Nguyen, Elizabeth
Abstract: Prior research suggests that prediction of semantic and syntactic information prior to the bottom-up input is an important component of language comprehension. Recent work in basic visual and auditory perception suggests that the ability to predict features of an upcoming stimulus is even more valuable when the exact timing of the stimulus presentation can also be predicted. However, it is unclear whether lexical-semantic predictions are similarly locked to a particular time, as previous studies of semantic predictability have used a predictable presentation rate. In the current study we vary the temporal predictability of target word presentation in the visual modality and examine the consequences for effects of semantic predictability on the event-related N400 response component, as measured with magnetoencephalography (MEG). Although we observe robust effects of semantic predictability on the N400 response, we find no evidence that these effects are larger in the presence of temporal predictability. These results suggest that, at least in the visual modality, lexical-semantic predictions may be maintained over a broad time-window, which could allow predictive facilitation to survive the presence of optional modifiers in natural language settings. The results also indicate that the mechanisms supporting predictive facilitation may vary in important ways across tasks and cognitive domains.